Radiocarbon Ages Constraints on the Origin and Shedding of Bank-Top Sediment in the Bahamas during the Holocene - Slowey, N; Henderson, G (2011)
Great quantities of fine-sized aragonite needles are produced in the shallow waters that cover the tops of the Bahama Banks and then exported to the bank margins where they accumulate with shells of pelagic organisms. To better understand these processes, we investigated Holocene-aged sediments in a core from the southwestern margin of Little Bahama Bank. The aragonite content of the sediments, δ18O of planktonic foraminifera shells, and radiocarbon ages of aragonite-rich <63 μm sediments and coexisting planktonic foraminifera shells were determined. Sediment deposition was rapid overall, and a significant increase in deposition rate occurred 3,500-4,000 years ago, shortly after rising sea level flooded the bank top with seawater and caused a dramatic increase in the shallow water area where aragonite production occurred. During the latest Holocene when high deposition rates minimize effects of bioturbation, aragonite-rich <63 μm sediments are 400-600 years older than coexisting foraminifera. This difference indicates the net age of aragonite when it was exported from the bank top. It is consistent with expectations of the "hip-hop'n" model (Morse et al. in Geochimica et Cosmochimica Acta 67: 2819-2826, 2003) whereby aragonite needles on the bank top, formed initially by biologic or other processes, continue to grow for hundreds of years via precipitation of epitaxial carbonate cement from seawater. Earlier in the Holocene, when sea level was lower and the top of Little Bahama Bank was subaerially exposed, the deposition rate and aragonite content of the sediments were less, and the aragonite-rich <63 μm sediments are about 1,000 years younger than coexisting foraminifera. This age difference can be explained by downward mixing of latest-Holocene <63 μm material into older early-Holocene sediments. © 2011 Springer Science+Business Media B.V.